The Importance of Parental Involvement on Students’ Speaking Achievement - Olivia Heluri Yolanda Putri; Hamamah Hamamah; Widya Caterine Perdhani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research article explores the importance of parental involvement on students’ speaking achievement. The researchers demonstrate how parental involvement in children’s learning process can lead to numerous benefits for both children and parents, educators, and also school; including speaking achievement in English subject area. In this global era, Indonesian students are expected to master English as stated in the curriculum. Speaking is an essential skill in English to help students facing the global era in order to build relationships with other people around the world. Sometimes students have difficulties in practicing their speaking skills. This may be due to the lack of involvement of parents in the children’s learning process. Parents should encourage their children to be fluent in English as one of the international languages which are needed to find a job and pursue further education. As a result, it is not only parents that become the crucial components in educating students to create a better achievement but also school and community matters. Thus, the involvement of parents is needed to play an active role in collaboration with school and community to help students to be actively participating in the learning process to increase students’ speaking achievement.